Recurrent glioblastoma metastatic to the lumbar vertebra: A case report and literature review: Surgical oncology - Matsuhashi, Ako; Tanaka, Shota; Takami, Hirokazu; Nomura, Masashi; Ikemura, Masako; Matsubayashi, Yoshitaka; Shinoda, Yusuke; Yamada, Keisuke; Sakai, Yu; Karasawa, Yasuaki; Takayanagi, Shunsaku; Saito, Nobuhito (Frontiers in Oncology, 2023)
(1) Background Glioblastoma is a malignant brain tumor, and its prognosis is as poor as 1.5 to 2 years. Most cases recur within one year even under the standard treatments with aggressive tumor resection and chemoradiotherapy. Majority of recurrences are local, and in rare cases, metastasize mostly within the central nervous system. Extradural metastasis of glioma is exceedingly rare. Here, we present a case of vertebral metastasis of glioblastoma. (2) Case presentation We present a 21-year-old man post total resection of the right parietal glioblastoma, diagnosed with lumbar metastasis. He originally presented with impaired consciousness and left hemiplegia and underwent gross total resection of the tumor. Given the diagnosis of glioblastoma, he was treated with radiotherapy combined with concurrent and adjuvant temozolomide. At 6 months after tumor resection, the patient presented with severe back pain, and was diagnosed as metastatic glioblastoma on the first lumbar vertebrae. Posterior decompression with fixation and postoperative radiotherapy were conducted. He went on to receive temozolomide and bevacizumab. However, at 3 months after the diagnosis of lumbar metastasis, further disease progression was noted, and his care was transitioned to best supportive care. Comparison on copy number status between primary and metastatic lesions on methylation array analysis revealed more enhanced chromosomal instability including 7p loss, 7q gain and 8 gain in the metastatic lesion. (3) Conclusion Based upon the literature review and our case, younger age of initial presentation, multiple surgical interventions, and long overall survival seem to be the risk factors of vertebral metastasis. As the prognosis of glioblastoma improves over time, its vertebral metastasis is seemingly more common. Therefore, extradural metastasis should be kept in mind in the treatment of glioblastoma. Further, detailed genomic analysis on multiple paired specimens is mandated to elucidate the molecular mechanisms of vertebral metastasis.